Strategi Pengasuhan PT. Pupuk Indonesia (Persero) - Asikin, Budi; Rusdi, Muhammad Arief; Munir, Ningky Sasanti (Journal of Management and Business Review, 2021)
As a large business entity that already has many subsidiaries, PT Pupuk Indonesia (Persero) is required to carry out a professional corporate governance system based on strong commercial principles, in the sense that it is able to provide added value, benefits and maximum profit levels to shareholders and existing stakeholders. Therefore, PT Pupuk Indonesia (Persero) needs to carry out an in-depth analysis of the implementation of the management strategy of its subsidiaries to determine the level of compatibility between the characteristics of the parent and its subsidiaries. Thus the company can develop a parenting strategy that is appropriate, effective and will further increase the value and competitiveness of the company as a whole. This research is an applied research with a qualitative descriptive approach using the Corporate Parenting Framework from Campbell et al. (1995). Data obtained through interviews, observation, and study of relevant documents. The study shows that the subsidiaries engaged in the main business of the fertilizer and chemical industry are in the Heartland Business category. Subsidiaries engaged in supporting businesses in the industry, trade and energy services sector, shipping and sea transportation and agricultural industry and trade are in the Edge of Heartland category. For subsidiaries engaged in EPC services and trading and general services the position is is in the area of the Alien Territory. So the parenting style of a parent company that is suitable for parenting for a subsidiary that falls into the Heartland Business category is a combination of corporate development and linkage influence; for a subsidiary that is part of the Edge of Heartland area, is stand alone influence. Meanwhile, for subsidiaries that are included in the Alien Territory area, the parenting style is linkage influence.